Design and construction of a low-cost acoustic measurement tube for material evaluation: methodology and structural validation (Ciencias de la Ingeniería y Aplicadas, 2026)
This paper describes the design and construction of an acoustic impedance measurement tube, also known as an acoustic impedance measurement tube, intended to evaluate the sound absorption behavior of alternative materials. The manufacturing process, material selection, and measurement system configuration are presented. Although measurements have not yet been performed, the necessary parameters for future experimental testing are established.
Keywords: Acoustic impedance; sound absorption; acoustic measurement